2012
DOI: 10.1063/1.4722994
|View full text |Cite
|
Sign up to set email alerts
|

Atomic behavior of carbon atoms on a Si removed 3C-SiC (111) surface during the early stage of epitaxial graphene growth

Abstract: The understanding of the formation of graphene at the atomic scale on Si-terminated 3C-SiC for obtaining high-quality graphene sheets remains elusive, although epitaxial graphene growth has been shown to be a well-known method for economical mass production of graphene/SiC heterojunctions. In this paper, the atomic behavior of carbon atoms on a Si removed 3C-SiC (111) surface for the formation of graphene buffer layer during the early stage of epitaxial graphene growth was investigated using a molecular dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Recently, significant theoretical efforts have been dedicated to understand the experimental observation for the graphene substrate on the SiC growth. For example, Tang and Hwang et al demonstrated that the graphene-like structure appears at temperatures higher than 1300–1500 K based on their simulation results with Tersoff potential. , Iguchi et al employed Brenner potential to study the effects of temperature and surface orientation on the quality of graphene . Besides, Nemec et al tried to reveal the reason of why graphene growth on the C-terminated SiC surface is very different with that on the Si-terminated face with the help of ab initio calculations .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, significant theoretical efforts have been dedicated to understand the experimental observation for the graphene substrate on the SiC growth. For example, Tang and Hwang et al demonstrated that the graphene-like structure appears at temperatures higher than 1300–1500 K based on their simulation results with Tersoff potential. , Iguchi et al employed Brenner potential to study the effects of temperature and surface orientation on the quality of graphene . Besides, Nemec et al tried to reveal the reason of why graphene growth on the C-terminated SiC surface is very different with that on the Si-terminated face with the help of ab initio calculations .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Zhang and van Duin carried out ReaxFF MD simulations to describe both the thermal decomposition of SiC substrates and the CVD growth of graphene layers with a focus on the different temperature regimes. More common results use Tersoff and Brenner interatomic potentials , to characterize the growing shapes of graphene nanostructures or study the effects of temperature or surface geometry . Meagre attempts of using ab initio methods include AIMD simulations of the decomposition of the first layers of SiC substrates or the study of nucleation of different graphene precursors on metallic substrates. , …”
Section: Introductionmentioning
confidence: 99%
“…10) The mechanism of graphene growth by SiC surface decomposition at the atomic level is not yet well understood. Many investigations of graphene using first-principles [11][12][13][14] and classical molecular dynamics (MD) [15][16][17] simulations have been reported. First-principles methods are powerful tools for the rigorous analysis of energetically stable structures, bonding sites, and band structures, among others.…”
Section: Introductionmentioning
confidence: 99%